SEKTOR INFORMAL SEBAGAI KATUP PENGAMAN PENYERAPAN TENAGA KERJA TIDAK TERAMPIL (UNSKILLED WORKERS) (KASUS PEDAGANG ANGKRINGAN DI KOTA YOGYAKARTA) - I Made Sarmita (Media Komunikasi Geografi, 2013)
This study focuses on angkringan trader profile relationship as a safety valveunskilled workers in the city of Yogyakarta. This study is a fundamental anddescriptive survey of 45 angkringan trader in Yogyakarta. The data were collectedthrough structured interviews and observation is further analyzed using adescriptive. The results showed that the majority of angkringan trader is a middleagedin labor force and dominated by men. The Highest level of education theyare able to accomplish is a elementary school, senior high school and junior highschools. Angkringan trader mostly local workers from Yogyakarta, some aremigrant workers who come from Klaten, and Gunung Kidul. Income that could beobtained ranged between Rp 600,000 - Rp 1,500,000 per month. A small part ofangkringan trader have side jobs as laborers and becak with additional incomebetween Rp 300,000-Rp 500,000 per month. The main reason they chose theseefforts are not require special skills. Angkringan is a safety valve in the absorptionof unskilled workers. This fact supported by the responses of respondents said anangkringan trader because required of skill is not too special. The positive impactof angkringan trader visible presence in the social and economic consequences offavorable economic growth and reduce the unemployment rate in the city ofYogyakarta. This Small businesses have proven to be invisible hand for economicdevelopment in the city of Yogyakarta.Keywords: Angkringan Trader, Safety Valve, Unskilled Workers